The 2nd International Conference of International Researchers of the Education for Environmental Citizenship 2022 - Hadjichambis, Andreas Ch; Reis, Pedro; Knippels, Marie-Christine; Telesiene, Audronė; Goldman, Daphne; Paraskeva-Hadjichambi, Demetra; Cincera, Jan; Jančaříková, Kateřina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Environmental Citizenship is a key factor for sustainability, green transition, and cycle economy, as well as a low-carbon society. Environmental Citizenship has been an influential concept in many different arenas, including education. Education for Environmental Citizenship (EEC) has a lot to contribute to this direction. The European Network for Environmental Citizenship (ENEC), which is active in 39 countries, established the biennial International Conference iREEC of "International Researchers on the Education for Environmental Citizenship". The 2nd iREEC 2022 includes original research papers, theoretical papers, and reports from around the world dealing with Education for Environmental Citizenship in all levels and settings.